The prehistoric hilltop settlement of Gradec near Blečji Vrh in Dolenjska - Pavlin, Primož (Arheološki vestnik, 2011)
The test excavations at Gradec near Blečji Vrh revealed that the hilltop site had been settled in several prehistoric periods. The earliest finds were either from the end of the Neolithic or the Copper Age, when the settlement was probably fortified for the first time with a stone wall. In the period of the Certosa fibula horizon, new wall was built on the ruins of the first rampart. Thick layers with iron slag show that at that time Gradec was an important iron working and metallurgic center. Existence at Gradec then ceased for a certain time. It was again populated in the earlier part of the Late La Tène (the Mokronog IIIa phase). At that point, the economy was also based on processing iron ore. Numerous fragments of fine pottery and amphorae for wine indicate the relative prosperity of the Late La Tène inhabitants of Gradec